Ternary Blend Strategy for Achieving High‐Efficiency Organic Photovoltaic Devices for Indoor Applications. Issue 24 (4th April 2019) - Singh, Ranbir; Shin, Sang‐Chul; Lee, Hansol; Kim, Min; Shim, Jae Won; Cho, Kilwon; Lee, Jae‐Joon
Abstract: Monomeric perylene diimide (PDI) small molecules display a high absorption coefficient and crystallinity in solid‐state thin films due to strong π–π interactions between the molecules. To take advantage of these exciting properties of PDIs, N, N '‐bis(1‐ethylpropyl)perylene‐3, 4, 9, 10‐tetracarboxylic diimide (EP‐PDI) was mixed with a binary blend of PTB7 and PC71 BM to fabricate an efficient ternary blend, which were in turn used to produce organic photovoltaic (OPV) devices well suited to indoor applications (PTB7=poly({4, 8‐bis[(2‐ethylhexyl)oxy]benzo[1, 2‐ b :4, 5‐ b ′]dithiophene‐2, 6‐diyl}{3‐fluoro‐2‐[(2‐ethylhexyl)carbonyl]thieno[3, 4‐ b ]thiophenediyl}), PC71 BM=[6, 6]‐phenyl‐C71 ‐butyric acid methyl ester). We varied the PC71 BM/EP‐PDI weight ratio to investigate the influence of EP‐PDI on the optical, electrical, and morphological properties of the PTB7:PC71 BM:EP‐PDI ternary blend. Compared with the reference PTB7:PC71 BM binary blend, the ternary blends showed strong optical absorption in the wavelength range in which the spectra of indoor LED lamps show their strongest peaks. The addition of EP‐PDI to the binary blend was found to play an important role in altering the morphology of the blend in such a way as to facilitate charge transport in the resulting ternary blend. Apparently, as a result, the optimal PTB7:PC71 BM:EP‐PDI‐based inverted OPV device exhibited a power conversion efficiency (PCE) of 15.68 %, a fill factor (FF) of 68.5 %, and short‐circuit current density ( J SC ) of 56.7 μA cm −2 under 500 lx (ca. 0.17 mW cm −2 ) indoor LED light conditions. Abstract : An efficient ternary blend system for application in indoor organic photovoltaic (OPV) devices has been developed. The ternary blend system PTB7:PC71 BM:EP‐PDI was designed to produce optimal OPV devices under indoor light‐emitting‐diode (LED) light conditions. The campion OPV device exhibited a high power conversion efficiency (PCE) of 15.68 % under 500 lx (ca. 0.17 mW cm −2 ) indoor LED light conditions.